LEADERS AND LEADERSHIP - Bratanov, Crina; Chirimbu, Sebastian (Annals of Spiru Haret University. Economic Series, 2013)
Leadership is the ability to transform vision into reality, and the leader is the architect who manages to turn what was just a projection of the future vision of the organization in a tangible reality. A leader can be a manager, while the manager is always a leader. If management function is carrying out particular activities under formal authority, leadership is more than authority and power. Add leadership vision, daring, personal effort and amount of unique qualities, personal, boosting process management.